Los nuevos instrumentos para la operación de la política social en México (2018-2024) - Cejudo Ramírez, Guillermo Miguel; Lugo Gutiérrez, Damián Ignacio (El Colegio de México A.C., 2025)
This article analyzes the design and implementation of four procedural instruments central to the operation of social policy under the administration of Andrés Manuel López Obrador: the so-called super-delegates, a new “Welfare Census”, the apparatus of social workers known as Servidores de la Nación (Servants of the Nation), and the Development Integration Centers. After describing the model that presumed their effective operation, we analyze the actual implementation of each of these components, drawing on official documents, news coverage, program evaluations, and the emerging academic literature on the subject. We contrast their expected operation with their actual deployment. We argue that their effectiveness varied significantly and that they required ongoing calibration during the administration, with some being discarded and others replaced. We conclude that these procedural instruments operate in a disjointed manner, failing to achieve necessary synergies for effective social program coordination: they fail to properly identify beneficiaries, characterize their needs, bring government services closer to people, deliver the goods or services, and monitor them.